Zero-fare tours through the lens of a fatal conflict. (December 2020) - Yan, Libo
Abstract: Forced shopping associated with zero-fare tours may cause conflicts between tour participants and local guides. This study applied the attribution theory to examine bloggers' online responses to a tragic event caused by forced shopping in Hong Kong, and the purpose was to explore why the zero-fare phenomenon is robust and who should be responsible for the unethical business. The stakeholders were identified and categorized into four types within a two-dimension (interest and influence) framework. The bloggers' attribution processes disclosed the causes and responsibility holders of zero-fare tours. The study results have implications for destinations that depend on a price-driven market. Highlights: Applies the attribution theory to analyze the causes of zero-fare tours. Adds to understanding of attribution by disclosing a collective attribution process. Reveals four types of stakeholders with the interest-influence framework. Finds that frauds involved in zero-fare tours are regarded as a destination attribute. Discloses the questionable roles that governments play in tourism governance.